Research Overview of the Rulings of Rebellion (Khurūj) in Sīrah Perspective - Muhammad Nasir; Bukhari, Syed Naeem Badshah (Journal of Islamic and Religious Studies, 2019)
Islam orders to obey the ruler and not to indulge in activities that may cause disruption & instability of an Islamic state. This research discusses rules & regulations based on sīrah about rebellion (khurūj), and relevant topics from Islamic Jurisprudence. The basic question of this research is whether revolt against the ruler is permissible and what would be the punishment? This research elaborates four types of rebellion. Rulings of Muslim scholars regarding rebellion are subjected to the different positions of rulers. According to all school of thoughts the khurūj is not permitted if the ruler is lawful and serving his community with justice. In contrary, there is difference of opinions about the tyrannous and iniquitous ruler. This article concluded that majority of Muslim Scholars do not permit khurūj in any case, some others laid down very strict conditions in this regard.